Women’s Anxiety and Fetal Movement in the 3rd Trimester of Pregnancy - Jannetia, Chindy Zulfanji; Yudianti, Ika; Yuliani, Ita (EMBRIO: Jurnal Kebidanan, 2023)
Pregnancy is an important period in a woman's life, where there are physiological and psychological changes as well as changes in their status in the family and society. These changes can cause mental disorders of various types, for example, increased stress and anxiety, as well as mood disorders. Maternal anxiety will cause interaction among hormones which leads to alteration of fetal wellbeing. This study aims to determine the correlation between anxiety and the frequency of fetal movement in the 3rd trimester of pregnancy. The subjects of this study were 30 at-risk pregnant women at a TPMB in Malang City, who were selected through consecutive sampling. Measurement of anxiety levels using the PRAQ-R2 instrument, as well as the Kick Counter application to calculate fetal movements. Each subject was observed using both instruments 3 times at intervals a week. The results of the study from 3 series of Chi-Square tests showed significant results, namely there was a correlation between the level of anxiety and the frequency of fetal movement in all measurements (p-value 0.033; 0.042; 0.047). Pregnant women with mild anxiety produce a normal frequency of fetal movements. Conversely, pregnant women with severe anxiety result in abnormal fetal movement frequency. It is recommended that every pregnant woman can maintain mental health so that fetal movements remain normal.